Creación e implementación de un portal web que incluya un repositorio de objetos de aprendizaje para el centro educativo de educación básica Rosa María Guzmán de Torres de la ciudad de Saraguro. - León Villacrés, Sandra América (2014)
The present research is a requirement to finish the career includes the creation and implementation of a web portal that includes a repository of learning objects (ROA) for the basic educational school "Rosa María Guzmán de Torres" that is located in Saraguro city which perspective is to maintain a constant communication between teachers, students, and community; also another objective is to provide a tool that facilitates the access to educational materials by using learning objects. In relation to the theoretical support described in the literature review section it was collected information and concepts of Web portals, content management systems, Joomla, repository of learning objects, Dspace, databases and development tools and the tools to be used in the development of the Portal and ROA were defined. In the phases of analysis, interpretation and valuation, it was applied surveys and interviews to teachers, students and parents of the school in order to collect information, in the development of the project it was used the UWE methodology. The Portal was implemented using the management contents system of Joomla, which pattern of development is the MVC (view controller model), with its manager database MySql, for ROA Dspace and Postgresql as Manager of the database. In the stage of results it was detailed the creation and implementation process of the Web Portal and the ROA domain www.rosamariaguzman.com, process applying the UWE methodology, in requirements analysis model are the content of Joomla, and Dspace Repository Case Model Using the Web Portal, at the stage of analysis and design models are described: content, navigation and presentation of Web Portal and Repository Learning Objects, and implementation; standardized testing, validation and acceptance by the user. In the discussion it was described how each one of the proposed objectives was accomplished at the beginning of the project. Finally, the conclusions and recommendations were presented. These conclusions and recommendations are the result of the experience gained during the development process.